On the Accuracy and Properties of Recent Macroeconomic Forecasts - Zarnowitz, Victor (American Economic Review, 1978)
The aim of this study is to contribute to the measurement and analysis of errors in economists' predictions of changes in aggregate income, output, and the price level. Small sample studies of forecasts can be instructive, but their limitations must be recognized. Compilation of consistent forecast records extending over longer periods of tine is necessary to establish a reasonably reliable base for assessments of forecasting behavior and. performance. Thus the historical record of post-World War II forecasts assembled in the 1960's by the NBER is here extended and updated.